Assessing key success factors of the Islamic banks in Malaysia: risk management perspective - Mohd. Ariffin, Noraini; Kassim, Salina (s.n, 2012)
This study aims to analyse the relationship between risk management practices and financial performance in the Islamic banks in Malaysia. In achieving this objective, the study assesses the current risk management practise of the Islamic banks and links them with the financial performance of the banks. The study uses both the primary (survey questionnaire) and secondary data (annual reports)